2013
DOI: 10.4049/jimmunol.1300426
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Signaling Regulates Innate and Adaptive Immunity to Cryptococcus neoformans

Abstract: Susceptibility to progressive infection with the fungus Cryptococcus neoformans is associated with an allergic pattern of lung inflammation, yet the factors that govern this host response are not clearly understood. Using a clinically relevant mouse model of inhalational infection with virulent C. neoformans H99, we demonstrate a role for IL-33–dependent signaling in host immune defense. Infection of BALB/c mice with 104 CFU of C. neoformans H99 caused a time-dependent induction of IL-33 with accumulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 54 publications
1
63
1
Order By: Relevance
“…In another study, ST2-deficient mice had improved survival and lower C. neoformans burdens in the lungs, spleen, and brain (61). The ST2 deficiency led to a decrease in production of IL-5 and IL-13 by innate type 2 lymphoid cells and impaired Th2 mucosal immunity (61).…”
Section: T Helper St2mentioning
confidence: 99%
“…In another study, ST2-deficient mice had improved survival and lower C. neoformans burdens in the lungs, spleen, and brain (61). The ST2 deficiency led to a decrease in production of IL-5 and IL-13 by innate type 2 lymphoid cells and impaired Th2 mucosal immunity (61).…”
Section: T Helper St2mentioning
confidence: 99%
“…Collectively, these mechanisms generate an environment that is dominated by anti-inflammatory markers such as IL-4 and IL-33 (REFS 3941), which, as a consequence, reduce cryptococcal killing by the immune system 38, 42 . Therefore, modulating natural immune responses to cryptococcal infection towards a more pro-inflammatory profile offers one potential avenue for treatment.…”
Section: Host Immunity and Pathogen Subversionmentioning
confidence: 99%
“…Although characteristics of ILCs that respond to IL-33 are still being delineated, recent studies have indicated that IL-33 induces production of large amounts of IL-5 and IL-13 by group 2 innate lymphoid cells (ILC2s) in several diseases models [50,[56][57][58] (Fig. 2).…”
Section: Il-33/st2l In Innate Lymphoid Cellsmentioning
confidence: 99%